THE EFFECT OF MANAGEMENT COMPENSATION, THIN CAPITALIZATION AND SALES GROWTH ON TAX AVOIDANCE WITH INSTITUTIONAL OWNERSHIP AS MODERATION - Hermi Hermi; Petrawati Petrawati (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
This study aims to examine the effect of management compensation, thin capitalization and sales growth with institutional ownership as a moderation on tax avoidance. The population used in this study is manufacturing goods sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The dependent variable is tax avoidance and the independent variable is management compensation, thin capitalization and sales growth. The moderating variable is institutional ownership. The control variables used are leverage, firm size. The sampling technique used was purposive sampling. The results of this study indicate that management compensation and thin capitalization have an effect on tax avoidance. Meanwhile, sales growth has no effect on tax avoidance. Institutional ownership can weaken the positive effect of management compensation, thin capitalization and sales growth on tax avoidance. This study also reveals that profitability and firm size control variables have an effect on tax avoidance.